Prehod v nizkoogljično družbo terja večjo rabo lesa - Koprivnikar, Mihael (Gozdarski vestnik, 2011)
Slovenia has set itself high goals in the field of renewable energy sources (RES). Along with attaining the strategic goals of greenhouse gas emissions reduction and political goodwill, chances for forest-wood sector development are manifesting at the moment. Following the example of Scandinavian countries and Austria, this sector can be one of the carriers of the low carbonsociety's sustainable economy and a challenge for creating new developmental opportunities. Among the questions the profession must answer for a clear and fast development of forestry and timber industry is also the question of quantity harvested for providing the economy of scope. Furthermore, new findings regarding higher wood stock and plans for recognition of carbon sink in Slovenian forests in the framework of the new climate agreement also require an extensive professional treatment. All this can heavily affect value increment fluctuation and final yield for the owner, wood processing industry and country.
Keywords: obnovljivi energetski viri; sustainable development; trajnostni razvoj; biomasa; les; forestry; gozdarstvo; lesarstvo; raba lesa; mobilizacija lesa; posek; lesna zaloga; prirastek; ogljik